2015
DOI: 10.4103/0976-0105.145776
|View full text |Cite
|
Sign up to set email alerts
|

Healing of burn wounds by topical treatment: A randomized controlled comparison between silver sulfadiazine and nano-crystalline silver

Abstract: Background:Silver sulfadiazine (SSD) has been the standard topical antimicrobial for burn wounds for decades. Recently, nanometer-sized silver particles are available which have high surface to volume ratio and remain effective even at a very low concentration and minimizes the chance for tissue toxicity due to silver. Hence, we conducted a randomized controlled trial to compare the effectiveness of topical SSD and nano-crystalline silver (AgNP) hydrogel in burn wounds management.Materials and Methods:Study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 19 publications
(24 reference statements)
2
54
0
3
Order By: Relevance
“…AgSD has dual antibacterial effects. The free silver can react with both sulfhydryl groups of bacterial enzymes and DNA, and sulfadiazine can stop the synthesis of DNA by interrupting the production of folate [7]. However, the antibacterial effect of AgSD is badly limited by its poor aqueous solubility [8].…”
Section: Introductionmentioning
confidence: 99%
“…AgSD has dual antibacterial effects. The free silver can react with both sulfhydryl groups of bacterial enzymes and DNA, and sulfadiazine can stop the synthesis of DNA by interrupting the production of folate [7]. However, the antibacterial effect of AgSD is badly limited by its poor aqueous solubility [8].…”
Section: Introductionmentioning
confidence: 99%
“…To circumvent this drawback, silver nanoparticles with high surface-to-volume ratio were synthesized which rendered these materials more efficient at low concentrations, thus resulting in reduced toxicity in comparison to traditional silver compounds. 69 It was demonstrated that pure silver nanoparticles were able to treat inflammation through cytokine modulation and induce wound healing with decreased scar formation. 35 Different shapes and sizes of silver nanostructures were also investigated and shown to achieve different degrees of antibacterial activity.…”
Section: Nanomaterials As Intrinsic Therapeutic Agentsmentioning
confidence: 99%
“…[3][4][5] As a result, most studies that use SSD as the control or comparator are biased in favor of the new treatment and almost always demonstrate that the novel therapy is superior to SSD. 13,14 It is our belief that to demonstrate superiority or even noninferiority, any therapy studied should be compared to an optimal comparator or standard of care. Because advanced silver-based dressings or petrolatum-based topical antibiotic ointments are often used but have not been directly compared head to head, we designed the current study to determine which was more effective in a previously validated porcine partial-thickness burn model.…”
Section: Discussionmentioning
confidence: 99%